Surface Modification of Poly(D,L-lactic-co-glycolic acid) Nanoparticles Using Sodium Carboxymethyl Cellulose as Colloidal Stabilizer - Chittasupho, Chuda; Thongnopkoon, Thanu; Kewsuwan, Prartana (Current Drug Delivery, 2016)
Poly(D,L-lactic-co-glycolic acid) nanoparticles (PLGA NPs) have been widely used as drug delivery systems for both small molecules and macromolecules. However, the colloidal stability problem remains unsolved. This study aims to investigate the possibility of using sodium carboxymethyl cellulose (SCMC) as a stabilizing agent of PLGA NPs. In this study, PLGA NPs were fabricated using various concentrations of SCMC (0.01, 0.1 and 0.5% w/v) by solvent displacement method. SCMC coated NPs were characterized using DLS, FTIR, DSC, colorimetric method. Particle size, polydispersity index, zeta potential values and SCMC adsorption increased with SCMC concentration. FTIR spectra, DSC thermograms and results of colorimetry suggested the interaction of SCMC and PLGA NPs. The stability of SCMC coated PLGA NPs was observed during the storage of three weeks in water. The stability of SCMC coated NPs in serum was also evaluated. Cell viability study revealed that there was no toxicity increased when SCMC was used as a stabilizing agent up to a concentration of 0.1% w/v. SCMC coated PLGA NPs bound A549 cells in a time dependent manner and with a greater extent than uncoated PLGA NPs. In conclusion, SCMC can be used to stabilize PLGA NPs by adsorbing on the surface of NPs.
Keywords: PLGA